Depression and risk-taking among adolescents in low- and middle-income countries - Ruiz Pozuelo, J (2022)
Depression and risky behaviours often co-occur and represent two critical –but often overlooked – public health concerns. This co-occurrence is particularly important during adolescence, a time when individuals make vital decisions with often long-lasting consequences for their health, overall well-being, and life chances.